Einkommensteuerbelastung ausgewählter Haushaltstypen in Deutschland 1958 bis 2013 - Alfred Boss; Hans Christian Müller; Axel Schrinner (Wirtschaftsdienst, 2014)
Die Steuerbelastung privater Haushalte ist auch nach der Bundestagswahl 2013 ein wichtiges Thema der wirtschaftspolitischen Diskussion in Deutschland. Die Autoren untersuchen, wie sich die Einkommensteuerbelastung im Laufe der Jahrzehnte entwickelt hat. – – The level of the income tax is a major issue of the political debate in Germany. The paper presents data on the income tax burden in the period 1958-2013. The data refer to specific levels of real income as well as to specifi c levels of income in relation to the average income. The discretionary changes to the income tax rates since 1958 have not suffi ced to avoid an increase in the marginal tax rates for typical taxpayers. As to the average tax rates, low income earners experienced a small decrease in their rates if their real income did not rise.
Keywords: H24; 330; Einkommensteuer; Steuerbelastung; Privater Haushalt; Deutschland